Five vs. six membered-ring PAH products from reaction of o-methylphenyl radical and two C3H4 isomers. Issue 27 (5th July 2021) - Shiels, Oisin J.; Prendergast, Matthew B.; Savee, John D.; Osborn, David L.; Taatjes, Craig A.; Blanksby, Stephen J.; da Silva, Gabriel; Trevitt, Adam J.
Abstract : Gas-phase o -methylphenyl reactions with propyne and allene form PAHs: with preferences for either six–six or five–six bicyclic products. Abstract : Gas-phase reactions of the o -methylphenyl ( o -CH3 C6 H4 ) radical with the C3 H4 isomers allene (H2 CCCH2 ) and propyne (HCC–CH3 ) are studied at 600 K and 4 Torr (533 Pa) using VUV synchrotron photoionisation mass spectrometry, quantum chemical calculations and RRKM modelling. Two major dissociation product ions arise following C3 H4 addition: m / z 116 (CH3 loss) and 130 (H loss). These products correspond to small polycyclic aromatic hydrocarbons (PAHs). The m / z 116 signal for both reactions is conclusively assigned to indene (C9 H8 ) and is the dominant product for the propyne reaction. Signal at m / z 130 for the propyne case is attributed to isomers of bicyclic methylindene (C10 H10 ) + H, which contains a newly-formed methylated five-membered ring. The m / z 130 signal for allene, however, is dominated by the 1, 2-dihydronaphthalene isomer arising from a newly created six-membered ring. Our results show that new ring formation from C3 H4 addition to the methylphenyl radical requires an ortho -CH3 group – similar to o -methylphenyl radical oxidation. These reactions characteristically lead to bicyclic aromatic products, but the structure of the C3 H4 co-reactant dictates the structure of the PAH product, with allene preferentially leading to the formation of two six-membered ring bicyclics and propyne resulting in the formation of six and five-membered bicyclic structures.